2019
DOI: 10.1155/2019/1690986
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Antenatal Care Visits Increase Institutional Delivery at Dabat Health and Demographic Surveillance System Site, Northwest Ethiopia

Abstract: Background. Early diagnosis of pregnancy, professional follow-up, and skilled delivery service are the main interventions that reduce maternal morbidity and mortality. Generating local based evidence could support targeted and effective intervention placed by a government. Therefore, determining the prevalence of skilled institutional delivery and its associated factors is of supreme importance. Methods. A community based cross-sectional study was conducted among pregnant women at Dabat Health and Demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 19 publications
5
20
2
Order By: Relevance
“…The number of ANC visits tended to increase the utilization of institutional delivery services. This finding is in line with those of other studies conducted in different parts of Ethiopia [33][34][35]. This can be partially explained by the fact that ANC visit is one of the contact points with health professionals and the more the ANC visits done, the better the probability of getting adequate information about danger signs and complications related to pregnancy and the importance of delivering at the health institutions.…”
Section: Discussionsupporting
confidence: 91%
“…The number of ANC visits tended to increase the utilization of institutional delivery services. This finding is in line with those of other studies conducted in different parts of Ethiopia [33][34][35]. This can be partially explained by the fact that ANC visit is one of the contact points with health professionals and the more the ANC visits done, the better the probability of getting adequate information about danger signs and complications related to pregnancy and the importance of delivering at the health institutions.…”
Section: Discussionsupporting
confidence: 91%
“…8 Early diagnosis of pregnancy, professional follow-up, and skilled delivery service are the main interventions that reduce maternal morbidity and mortality. 9 Several studies revealed that increasing institutional delivery is a good strategy for reducing maternal morbidity and mortality. 8,[10][11][12][13] The factors associated with institutional delivery are multiple and include age, income status, education, occupation, religion, residence, attending ANC, frequency of ANC visit, age at first marriage, age at first pregnancy, types of pregnancy (planned/unplanned), gravidity, parity, owing radio and/or television, knowledge, and occurrence of pregnancy danger signs.…”
Section: Introductionmentioning
confidence: 99%
“…8,[10][11][12][13] The factors associated with institutional delivery are multiple and include age, income status, education, occupation, religion, residence, attending ANC, frequency of ANC visit, age at first marriage, age at first pregnancy, types of pregnancy (planned/unplanned), gravidity, parity, owing radio and/or television, knowledge, and occurrence of pregnancy danger signs. 1,2,5,8,9,[14][15][16][17][18][19][20][21][22][23] Ethiopia is one of the six countries that contribute to more than 50% of global maternal deaths. 24 Despite it is known that delivery attended by a skilled provider at a health facility reduced maternal deaths, but more than half of all births in Ethiopia take place at home.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal mortality due to complications of child birth in sub Saharan African countries is the highest, accounts about 66% from the total mortality in the globe (1). Evidences showed the most common causes of maternal mortalities can be prevented through quality of ANC ( antenatal care ) (2).World health organization recommended all pregnant women should provide the focused ANC services within the first trimester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%